Ma'ālāt al-Af‘āl ‘inda al-Imām al-Sālimī min khilāl Kitābih al-Jawābāt: Dirāsah Taṭbīqīyah fī Bāb al-Siyāsah al-Syar‘īyah - Al-Awaidi, Mahmoud bin Saeed bin Khalfan; Almujahed, Muhammad Said (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
The research aims to study the consequences of actions as the objective framework that guarantees the integrity of the work of the mujtahid in downloading rulings on the actions of those who are responsible. This study came to answer the following questions: What is the reality of the concept of consequences of actions? Is it legally valid? What is the effect of the consequences of the actions in the answers of Al-Salmi in Sharia politics? What is the extent of the presence of the consequences of actions in the answers of Imam Al-Salmi and his fatwas related to Sharia politics? The research has reached results, perhaps the most important of which are: the consequences of actions derive their legitimacy from the Qur’an and Sunnah, and it is not possible to download judgment on the actions of the taxpayers and their actions by simply looking at the incident without looking at its expected results in the future, and that Al-Salmi employed the origin of the consequences of actions in his answers in directing some of the sayings of scholars And in explaining his sayings, the presence of the origin of the consequences of actions and its fundamentalist, jurisprudential, and intentional rules is noted in his various answers related to Sharia politics.